RELIGIUSITAS NASKAH DRAMA KAPAI-KAPAI KARYA ARIFIN C NOER (Dialog Tokoh, Kakek dan Koor) - Mutia, Tuti (EDUKASI KULTURA JURNAL BAHASA SASTRA DAN BUDAYA, 2016)
The purpose of this study was to describe the values contained in the Religion plays Kapai-kapai Arifin C Noer work. The method used in this study is deskriptif analysis method. The subject of this study, that the play wright Relgiusitas Kapai-kapai Arifin C. Noer’s work, and as the object of study is a play Kapai-kapai. Data collection techniques in this study using the method of determining the unit of analysis, data recording, and the process of inference and analysis.The results can be the authors conclude that religiosity in a play Kapai-kapai Arifin C. Noer’s work includes: First, authentic religiosity or religiousness is directly coming from the heart. Includes prosecution toward better, please help and spiritual attitudes (conscience), seen very clearly in Abu dialogue and Grandfather. Both religiosity religious or indirectly in response to God, man passes through a particular religion is formal and official. Clearly visible on the dialog Grandfather and Abu. The level of religiosity Grandfather has more value than Abu. According Abu happy to be gained when we merge with God. In essence, religiosity was looking nature of God. If you want to know God then had to go into it (religion), then just know God